Identification of Germline Mutations in Upper Tract Urothelial Carcinoma With Suspected Lynch Syndrome - Guan, Bao; Wang, Jie; Li, Xuesong; Lin, Lin; Fang, Dong; Kong, Wenwen; Tian, Chuangyu; Li, Juan; Yang, Kunlin; Han, Guanpeng; Wu, Yucai; He, Yuhui; et al. (Frontiers in Oncology, 2022)
Objective Whole-exon sequencing (WES) is a commercially available tool for hereditary disease testing. However, little is known about hereditary upper-tract urothelial carcinoma (UTUC) in the Chinese population. This study aims to investigate the prevalence of Lynch syndrome (LS) in UTUC patients with high-risk features and identify the germline mutations of genetic predisposition gene mutations in those patients. Methods In total, 354 consecutive UTUC patients undergoing surgery were universally recruited, of whom 108 patients under 60 years old or with a personal/family history of cancer underwent universal immunohistochemistry staining to detect the expression of mismatch repair (MMR) proteins (MLH1, MSH2, MSH6 and PMS2). Patients with deficient or weak MMR protein staining or meeting the Amsterdam II criterion were defined as suspected LS patients, who further experienced microsatellite instability (MSI) (BAT25, BAT26, BAT40, D2S123, D5S346, D17S250) detection and performed WES analysis to explore germline pathogenic/likely pathogenic (P/LP) alterations. Results Of 108 patients, 90 (83.3%) cases were included due to younger than 60 years, and 18 cases due to personal/family history. IHC staining identified 21 patients with deficient MMR protein staining and 15 cases with weak MMR protein staining. Three cases met the Amsterdam II criterion but with proficient MMR protein staining. Finally, WES analysis was performed in 38 suspected LS patients and P/LP germline mutations were identified in 22 individuals. Genetic testing confirmed 5 LS cases, including 3 cases with novel mutations. MSI-harboring tumor was discovered in 4 LS cases, one of whom had weak MMR protein staining. Germline P/LP variants in DNA damage repair genes were found in 11 cases. In addition, we found that 11 patients had high- or moderate- penetrance P/LP mutations other than MMR genes. The common P/LP variants in high- or moderate-penetrance genes were 4 in ATM, 3 in MSH6 and KIT, and 2 in APC, NF1 and DICER. Conclusions We identified approximately 11% of UTUC cases as suspected LS and at least 1.4% patients with confirmed LS-associated UTUC. In addition, broader germline genetic testing could be considered to screen for cancer severity in hereditary UTUC patients.